2020
DOI: 10.1002/joc.6841
|View full text |Cite
|
Sign up to set email alerts
|

Cloud cover changes driven by atmospheric circulation in Europe during the last decades

Abstract: Due to its complex role within the radiation budget of the Earth, cloud cover plays an important role in climate variability at local, regional or continental scale. Consequently, there is a need for better understanding the causes and feedbacks of changes in cloud cover. We aim at investigating the response of cloud cover to changes in atmospheric circulation for 1981-2014. This is done based on the application of automated weather type classification from COST733 synoptic classifications software, which help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…On the other hand, needles from Transect 3 (Norway) tended to have a lower SD proj than what was expected based on MAT alone. Those were sites with high MAP and high cloud cover (Sfîcă et al, 2021), both of which would be consistent with reduced irradiance sums, perhaps also contributing to the low SD proj . Collectively, the observed patterns indicate that MAP may play a secondary role at best in determining SD across the Scots pine range.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, needles from Transect 3 (Norway) tended to have a lower SD proj than what was expected based on MAT alone. Those were sites with high MAP and high cloud cover (Sfîcă et al, 2021), both of which would be consistent with reduced irradiance sums, perhaps also contributing to the low SD proj . Collectively, the observed patterns indicate that MAP may play a secondary role at best in determining SD across the Scots pine range.…”
Section: Discussionmentioning
confidence: 82%
“…(2014)—pointing to decreasing cloud cover in winter, summer and spring, which is affecting the surface energy balance—, and by Sfîcă et al . (2020) who found a decrease in the cloud cover over the inner European continent and particularly in Eastern Europe. The substantial summer warming, especially daytime (TMAX), could be linked to the increase in meridional circulation (Seep and Jaagus, 2002) and higher persistence of anticyclonic circulation types (Barbu et al ., 2016), in combination with the increasing frequency in easterly circulation (Bartoszek, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Day-today changes in minimum and maximum temperatures are usually the highest between the second and fourth day of occurrence of a given circulation, and then they decrease or even change the sign to the opposite one [27]. Sfîcă et al [18] identified two major spatial changes in cloud cover over Europe, in connection with atmospheric circulation, associated with the latitudinal shift towards the north of the westerly circulation. The changes in cloud cover distribution and also in radiation fluxes leading to temperature changes, imposed by these shifts in atmospheric circulation over the continent, are higher in Eastern and Central Europe.…”
Section: Influence Of Atmospheric Circulationmentioning
confidence: 99%
“…Clouds and aerosols continue to contribute the largest uncertainty to estimates and interpretations of the Earth's changing energy budget [17]. The changes of atmospheric circulation in Europe during 1981-2014 were accompanied generally by a reduction of the total cloud cover over the continent, and this leads to an overall increase of the shortwave incoming radiation at continental scale causing a possible increase of air temperature [18].…”
Section: Introductionmentioning
confidence: 99%